2021
DOI: 10.1186/s13098-021-00690-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum fatty acid-binding protein 4 levels and responses of pancreatic islet β-cells and α-cells in patients with type 2 diabetes

Abstract: Background Serum fatty acid-binding protein 4 (FABP4), as an intracellular lipid chaperone and adipokine, was reported to be related to the incidence of type 2 diabetes (T2D) and diabetic complications, but its association with pancreatic islet β-cell and α-cell functions has not been fully elucidated. So the present study was to investigate the serum FABP4 levels and responses of islet β-cells and α-cells in patients with T2D. Methods 115 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…FABP4 and fatty acids promote and regulate insulin secretion during obesity [36,37]. Moreover, FABP4 has been correlated with C-peptide [37], which denotes endogenous insulin production [38]. Our results confirmed the association of FABP4 and C-peptide levels.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…FABP4 and fatty acids promote and regulate insulin secretion during obesity [36,37]. Moreover, FABP4 has been correlated with C-peptide [37], which denotes endogenous insulin production [38]. Our results confirmed the association of FABP4 and C-peptide levels.…”
Section: Discussionsupporting
confidence: 82%
“…Apart from BMI, FABP4 has been associated with other markers and risk factors for adiposity, for example, triglycerides, leptin, and cholesterol levels [26,[33][34][35]. FABP4 and fatty acids promote and regulate insulin secretion during obesity [36,37]. Moreover, FABP4 has been correlated with C-peptide [37], which denotes endogenous insulin production [38].…”
Section: Discussionmentioning
confidence: 99%
“… 29 Increased serum FABP4 levels were found to be closely associated with insulin resistance and elevated fasting and post-challenge glucagon levels in T2DM. 30 In this study, we also found that the baseline level of FABP4 was higher in participants with AGM than in those with NGT, and the baseline level of FABP4 was positively correlated with age, BMI, WC, 2hBG, TG, TC and LDL at the 2-year follow-up. Furthermore, we found that high baseline FABP4 [OR 0.960, 95% CI (0.928–0.993)] was not conducive to reversion from prediabetes to NGT.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, increased CysC concentration may induce an inflammatory response by enhancing TNF-α expression ( 30 , 49 ), and inflammation may in turn lead to β-cell dedifferentiation ( 50 , 51 , 52 ), characterized by loss of β-cell identity and expression of glucagon in these β-cells ( 53 ). Moreover, our previous study has demonstrated that fatty acid-binding protein 4, an inflammatory factor primarily originated from adipose tissue, was positively associated with fasting and postprandial glucagon levels in T2D ( 54 ). Collectively, our present study and the relevant literatures indicated that increased serum CysC levels may be contributed to the elevated fasting and postprandial glucagon in patients with T2D.…”
Section: Discussionmentioning
confidence: 99%